Platelet-lymphocyte ratio predicts chemotherapy response and prognosis in patients with gastric cancer undergoing radical resection - Zeng, Qingnuo; Wang, Shilong; Bai, Zilong; Nie, Yuanhua; Xu, Longwen; Chang, Dongmin (Frontiers in Oncology, 2024)
Background: Amounting literatures have reported the significance of systemic inflammatory markers for evaluating tumor prognosis. But few studies have systematically compared their superiority and their impact on adjuvant chemotherapy.We aimed to investigate the ability of inflammatory markers to predict the efficacy of chemotherapy in patients with GC treated with curative treatment and to identify an effective method that would allow clinicians to differentiate between chemotherapy-responsive populations.We retrospectively enrolled 730 GC patients who underwent radical gastrectomy. Fibrinogen (FIB), platelet-lymphocyte ratio (PLR), systemic inflammation response index (SIRI), prognostic nutritional index (PNI), systemic immune-inflammation index (SII), neutrophil-lymphocyte ratio (NLR) and lymph node ratio (LNR) were grouped according to cutoff values. Their clinical significance for GC prognosis was determined by multivariate COX regression analysis in both overall and subgroups by PLR status. Cases were divided into four groups according to PLR status and adjuvant chemotherapy status and survival was compared between groups.Results: Multivariate analysis showed that PLR was an independent prognostic factor for overall survival (OS) and disease-free survival (DFS) of GC patients. Adjuvant chemotherapy improved survival more significantly in patients with low PLR than that with high PLR. Among patients receiving adjuvant chemotherapy, low PLR was significantly associated with prolonged survival in TNM stage II, but not in TNM stage III.Preoperative high PLR is an independent risk factor for GC patients undergoing radical gastrectomy and adversely affects the postoperative chemotherapy effect.